modernization of Islamic studies curriculum in (fathul polar program) for the fifth grade at Pondok Modern Darussalam Gontor - Akrim Mariyat; Syekha Anintya Inayatusufi (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2022)
Boarding school is a subculture of Islamic education in Indonesia. For the sake of increasing public confidence towards the institutions of boarding school and keeping the identity of idealist of boarding school, a boarding school in fact needs a modernization of the existing system. With a modern system that should be able to establish the dynamic that has been created. One in system of review Islamic classic book, the typical education is an characteristic that owned by every boarding school. The methods used in studying the book of classic cottage in the salaf usually tend to use methods bendongan, translation, and sorogan. Modern Islamic boarding school Darussalam Gontor for girl second campus in review an Islamic classic book has put lot of effort to do in the application of modern system and some innovation. By carrying out activities Islamic classic books studies for class 5 KMI. This research is a qualitative research, used three method of data collection those are: 1. Interview, 2. Observation, 3. documentation. For data analysis researcher use method Miles and Huberman covering three step those are: data, collecting, data reduction, and conclusions. The purpose of this research is to know the methods of Modern Islamic Boarding School Darussalam Gontor especially Modern Islamic Boarding School Gontor for Girls 2 in forming good method in order to maximize the student in Islamic studies. The result of this study show: 1. That the implementation of existing Islamic classical books studies at Gontor for girl 2 was carried out in a systematic and organized, such as the activities of the participant should come on time with official uniform and each activity gets the direct supervision of the supervising and managing the activities of the committee. 2. Modernization of the implemented Modern Islamic Boarding School Darussalam Gontor for girls 2 in the implementation of the activities at each Islamic classical books studies components, they are: 1) Supervisor of the activities have a position as a leader and evaluator 2) The participant are self taught to learn the Islamic classic book 3) That utilize a whiteboard, projector, and notebook 4) To learn Islamic classic book use methods of problem solving and discussion.